If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + 12) = -3x + 6 Reorder the terms: 4(12 + x) = -3x + 6 (12 * 4 + x * 4) = -3x + 6 (48 + 4x) = -3x + 6 Reorder the terms: 48 + 4x = 6 + -3x Solving 48 + 4x = 6 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 48 + 4x + 3x = 6 + -3x + 3x Combine like terms: 4x + 3x = 7x 48 + 7x = 6 + -3x + 3x Combine like terms: -3x + 3x = 0 48 + 7x = 6 + 0 48 + 7x = 6 Add '-48' to each side of the equation. 48 + -48 + 7x = 6 + -48 Combine like terms: 48 + -48 = 0 0 + 7x = 6 + -48 7x = 6 + -48 Combine like terms: 6 + -48 = -42 7x = -42 Divide each side by '7'. x = -6 Simplifying x = -6
| 6b-23=2 | | 3(x+4)-5=37 | | 2x/3+10=x/5+36/5 | | 4y+2x-200=0 | | 5x+3y=8x-7 | | -6t-8-t=5+t | | 4(7-3m)=36 | | -6t-8-t=5-t | | 3x-7=8x-7 | | 2x+13=28-x | | -9x+7(x-2)+3x=-15 | | -7.5g=-6.66666666666666666 | | 5x-2=x+12 | | -2=3-6r+5r | | 0=-6(2k+2) | | 3x+2=8-x | | 2(x+1)=-5(2x-3) | | 5x-35y=-30 | | 4+7x=-20+3x | | 4x+15=26-3x | | 7(1-7x)=56 | | -9=21+3x | | y+1=6(x-5) | | -6m^2-13m+15= | | d^2-18d+80=0 | | 8(x-2)=3x-6 | | 2m-7=-8+m+1+3m | | 7(x-4)+10=2-3x | | 187-v=277 | | -2x+7x=-20 | | 3p+5p=72 | | 3+4x=36+3 |